Preparation of social workers for professional activity in the field of health: implementation of progressive ideas of the USA in Ukraine - Klos, Liliia (Social work and education, 2021)
The relevance of the study is due to the growing importance of health in the value system of modern society, as well as the deteriorating health of the population not only in Ukraine but in the world as a whole. The situation has especially deteriorated in the context of the coronavirus infection pandemic, which has led to the emergence of numerous new and exacerbation of "old" social problems of the population. Social workers cannot stay away from the problems faced by ordinary citizens, especially when it comes to achieving social justice and respect for human rights, in particular in such a sensitive area as health. To ensure the effective provision of social services and to address the social problems of the population on the basis of health, social workers must be properly prepared for this type of professional activity. The training of social workers for health activities in Ukraine is a fairly new and not very common area of training in higher education institutions, and the practice of social workers in the field of health care in Ukraine is not yet a typical phenomenon. The use of progressive foreign developments is a good basis for quality preparation of future and already practicing social workers for health activities. Of particular importance is the American experience in training social workers to work in health care, based on more than a century of practice in this area. In order to borrow and adapt the valuable ideas of foreign experts, a comparison of the training of social workers for health activities in the United States and Ukraine was made. On the basis of the revealed common and distinctive features the ways of introduction of the best achievements of the American high school in domestic practice of preparation of social workers are offered.